Incorporating Dance into Primary School Music Education: A Perspective on China’s New Curriculum Standards - Wu, Rui (Quality in Sport, 2025)
Under the “New Curriculum Standards”, the teaching of music and dance in primary schools urgently needs reform. As a new teaching method, module teaching is very suitable for the teaching of music and dance in primary schools under the background of “New Curriculum Standards”. It is conducive to enriching students’ artistic experience and to highlighting their learning initiative. The application strategies of module teaching in primary school music and dance mainly include: design of teaching modules; stimulating students’ independent learning with interest; encouraging students to communicate and cooperate to consolidate learning results and expand innovation, and making teaching life-oriented.